Efeitos da incorporação do extrato da semente do urucum em coberturas ativas à base de quitosana na carne bovina - Fonteles, Uri Vanille Raiol da Silva (2019)
The meat goes through several passive processes of contaminations, being important the search for efficient preservatives and that do not cause damages to the health of the consumer. Therefore, the uses of active toppings with natural extracts can add value to the product and even increase its shelf life. Therefore, the objective of this research was to evaluate the effects of the incorporation of the annatto seed extract into active chitosan - based coatings in beef. For the research the meat was submitted to CO treatments: marinated meat with distilled water; CQ: meat wrapped in chitosan and glycerol-based coating; EU4%: meat wrapped in chitosan base cover, glycerol and 4% urucum extract; EU8%: meat packed in chitosan, glycerol and 8% urucum extract. With regard to the characterization of the films, analyzes of thickness, solubility, moisture absorption, PVA, tension, deformation, light absorption, luminosity, color a *, color b * and MEV were performed, being possible to observe a reduction of water absorption and solubility of the films, in treatments EU4% and EU8%, one of the desirable factors when working with meat, because they release a lot of exudate. Microbiological analyzes of Coliformes at 45 ° C, total psychrotrophic counts, aerobic mesophilic bacteria, Staphylococcus spp. and Salmonella spp and physicochemical color, texture, pH, WHC and CL, which were analyzed at times zero, 2, 4, and 8 days of cold storage at 4 ° C ± 1º.¬ The meat with the treatments had lower scores microbiological tests when compared to control meat, with emphasis on the EU4% and EU8% treatments, which were effective throughout the shelf life studied. Regarding the physico-chemical analyzes, the results were satisfactory with the use of the CQ, EU4% and EU8% treatments as well as for the chemical analyzes of TBARS. Therefore, the use of chitosan-based toppings and urucum extract proved to be a viable and effective alternative to provide a microbiological and antioxidant health while maintaining the physicochemical characteristics when the treatments were inserted, during the whole shelf-life, being able to minimize the the use of synthetic antioxidants and enhance meat safety